First Direct Observations of Propagation of Discrete Chorus Elements From the Equatorial Source to Higher Latitudes, Using the Van Allen Probes and Arase Satellites. Issue 10 (23rd October 2020) - Colpitts, Chris; Miyoshi, Yoshizumi; Kasahara, Yoshiya; Delzanno, Gian Luca; Wygant, John R.; Cattell, Cynthia A.; Breneman, Aaron; Kletzing, Craig; Cunningham, Greg; Hikishima, Mitsuru; Matsuda, Shoya; Katoh, Yuto; et al.
Abstract: Whistler mode chorus waves have recently been established as the most likely candidate for scattering relativistic electrons to produce the electron microbursts observed by low altitude satellites and balloons. These waves would have to propagate from the equatorial source region to significantly higher magnetic latitude in order to scatter electrons of these relativistic energies. This theoretically proposed propagation has never been directly observed. We present the first direct observations of the same discrete rising tone chorus elements propagating from a near equatorial (Van Allen Probes) to an off‐equatorial (Arase) satellite. The chorus is observed first on the more equatorial satellite and is found to be more oblique and significantly attenuated at the off‐equatorial satellite. This is consistent with the prevailing theory of chorus propagation and with the idea that chorus must propagate from the equatorial source region to higher latitudes. Ray tracing of chorus at the observed frequencies confirms that these elements could be generated parallel to the field at the equator, and propagate through the medium unducted to Van Allen Probes A and then to Arase with the observed time delay, and have the observed obliquity and intensity at each satellite. Key Points: We present the first direct observation of the same discrete rising tone chorus elements propagating from a near equatorial to an off‐equatorial satellite Chorus is observed first on the more equatorial satellite, and is more oblique and significantly attenuated at the off‐equatorial satellite Ray tracing confirms possible generation at the equator and unducted propagation with the observed time delay, obliquity, and intensity